1996
DOI: 10.1074/jbc.271.43.26783
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid-induced Transcriptional Modulation of the Human Interferon-γ Promoter

Abstract: Disregulation of vitamin A metabolism is able to generate different immunological effects, including altered response to infection, reduced IgG production, and differential regulation of cytokine gene expression (including interleukin-2 and -4 and interferon-gamma (IFN-gamma)). In particular, IFN-gamma gene expression is significantly affected by vitamin A and/or its derivatives (e.g. retinoic acid (RA)). Here, we analyze the effect of retinoic acid on IFN-gamma transcription. Transient transfection assays in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 86 publications
2
35
0
1
Order By: Relevance
“…The proximal element has been shown to be a target for selective hypomethylation in cells that express IFN-␥ (43) and is believed to generate activation-specific expression in T-cell lines through binding of jun/ATF-2 heterodimers to this element (10). These sites are targets for selective inhibition of IFN-␥ gene transactivation after glucocorticoid treatment (8), but not following retinoid treatment (44,45). Additionally, whereas these sites are critical in regulation in PBL and T cell lines, they are of modest importance in modulating CD2 response in LPMC.…”
Section: Discussionmentioning
confidence: 99%
“…The proximal element has been shown to be a target for selective hypomethylation in cells that express IFN-␥ (43) and is believed to generate activation-specific expression in T-cell lines through binding of jun/ATF-2 heterodimers to this element (10). These sites are targets for selective inhibition of IFN-␥ gene transactivation after glucocorticoid treatment (8), but not following retinoid treatment (44,45). Additionally, whereas these sites are critical in regulation in PBL and T cell lines, they are of modest importance in modulating CD2 response in LPMC.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the role of specific activators of hormone nuclear receptors has been studied in these cells, and they were shown as useful and powerful modulators of proinflammatory cytokines and surface receptor ligands (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Surprisingly, two putative hormone response elements, retinoic acid and estrogen receptor binding motifs, which belong to the nuclear receptor superfamily of hormoneinducible transcription factors, had also been generated by the À179T allele. These were of particular interest in light of early studies, which had identified regulation of IFNG promoter expression by glucocorticoids, as well as vitamins A and D. 20,21 Competition experiments were carried out with consensus oligonucleotides to the various potential cis-acting elements (Figure 4). Table 1 summarizes the results of these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies have established transcriptional binding sites modulating IFN-g expression through members of the nuclear hormone receptor family such as glucocorticoid, vitamin D 3 and retinoic acid. 20,21,31 The estrogen receptor is an inducible trans-activating protein, which initiates transcription through the binding to DNA response elements defined as EREs, following exposure to estrogen. Hormone response elements for the various hormones, such as glucocorticoids, retinoic acid and estrogen, share sequence homology similarities, although each possesses distinct DNA binding sequence requirements.…”
Section: Discussionmentioning
confidence: 99%